Fermentation Improves Protein Content and Physicochemical Characteristics of Tempe Protein Concentrate Compared to Soy Protein - Astawan, Made; Yalmaida, Nabila Az Zahra; Damayanti, Aprilia Firdha; Prayudani, Ayu Putri Gitanjali; Saraswati, Saraswati; Wresdiyati, Tutik (Indonesian Food Science and Technology Journal, 2025)
The growing demand for sustainable plant-based proteins has increased interest in fermented soy products due to their improved nutritional and functional properties. This study investigated the effect of fermentation on the physicochemical and functional properties of tempe protein concentrate (TPC) compared to conventional soy protein products. Soybean flour (SF), soybean protein concentrate (SPC), tempe flour (TF), and TPC were produced and analyzed for proximate composition, antioxidant activity, physicochemical and functional properties. Soybeans and tempe were processed into flours, and protein concentrates were obtained by hexane defatting. Fermentation significantly increased protein content and bioactivity, as TF had higher protein content (48.27%) and antioxidant activity (58.54 mg AEAC/100 g) than SF. The concentration process further increased protein levels while reducing fat content, with TPC showing the highest protein content (68.80%), exceeding SPC (57.10%). TPC also exhibited improved physicochemical characteristics, including lower water activity (0.38), higher bulk density (0.51 g/mL), and better flowability (angle of repose 20.60o), suggesting improved stability and processability. Functional properties such as water absorption, oil absorption, and foaming capacity were significantly higher in both protein concentrates compared to their respective flours, although no significant differences were observed between TPC and SPC. These improvements are attributed to structural modifications during defatting, which increase protein solubility and expose hydrophilic and hydrophobic groups. These findings indicate that fermentation can improve the application and nutritional quality of soy protein products, supporting the development of functional foods and sustainable plant-based protein formulations.